To solve this problem we will apply the kinematic equations of angular motion that relate the variables to those of linear motion.
We know that acceleration is equivalent to
[tex]a=\omega^2*r[/tex]
Here,
[tex]\omega = \text{Angular velocity}[/tex]
r = Radius
At the same time the tangential velocity can be related with the angular velocity as follow,
[tex]v=\omega*r[/tex]
Our total value of acceleration is 4g, where g means the gravitational acceleration, then 4g is equal to
[tex]g=9.81m/s^2[/tex]
[tex]4g= 39.24 m/s^2[/tex]
The total value of this acceleration replacing it in our first equation would be,
[tex]39.24=\omega^2*r[/tex]
And the velocity in our second equation is
[tex]600=\omega*r[/tex]
[tex]r=\frac{600}{\omega}[/tex]
Replacing the value of r, we have
[tex]39.24=\omega^2(\frac{600}{\omega})[/tex]
Solve for [tex]\omega[/tex] and we get;
[tex]\omega=0.0654[/tex]
Replacing the angular velocity value in the linear velocity equation we will have that the radius is
[tex]600=\omega r[/tex]
[tex]600 =0.0654r[/tex]
[tex]r=9174m \approx 9200m[/tex]
Therefore the correct answer is B